PENGARUH STUDI KELAYAKAN BISNIS TERHADAP STRATEGI PENGEMBANGAN USAHA FORE COFEE - Nazhan Zahira; Dini Vientiany; Fridea Ramadhani; Dwi Febrina; Putri Afiqah Binti Ahmad (CV. Barokah Publsiher, 2025)
This research goals to analyze the impact of business feasibility studies on the business development strategy of Fore Coffee. A business feasibility study is an important managerial instrument used to evaluate the viability of a business prior to its development or expansion. A comprehensive feasibility assessment is predicted to assist management in formulating appropriate and sustainable business development strategies. The study employs a quantitative approach using a survey method. The independent variable the business feasibility study, which is measured through nine aspects: legal, market and marketing, technical and operational, management and human resources, financial, social, economic, environmental, sharia aspects. The dependent variable is the business development strategy. Surveys were conducted through the use of questionnaires featuring a Likert scale directed at participants pertinent to the study topic. The gathered data underwent linear regression analysis to assess the influence of the independent variable on the dependent variable. The outcomes indicate that business feasibility studies have a positive significant effect on the business development strategy of Fore Coffee. This finding suggests that the better the implementation and fulfillment of business feasibility aspects, the more effective the business development strategies formulated and applied by management. This analysis is believed to add value to the management academic community and practically serve as a consideration for business practitioners in developing sustainable business strategies.